2003
DOI: 10.1248/cpb.51.365
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Constituents from Umbelliferae Plants. VI. New Ursane-Type Saikosaponin Analogs from the Fruits of Bupleurum rotundifolium.

Abstract: The MeOH extract of the fruits of Bupleurum rotundifolium showed inhibitory activity against human gastric adenocarcinoma (MK-1) cell growth (GI(50): 6.25 microg/ml). From this extract, 10 new ursane-type triterpene glycosides viz. three 3-O-triosides (called rotundifoliosides A, I, and J) of 13beta,28-epoxy-3beta,16alpha-dihydroxyurs-11-ene, two (G and H) of 13beta,28-epoxy-3beta,16alpha,23-trihydroxyurs-11-ene, two (E and F) of 13beta,28-epoxy-3beta,16alpha,21beta-trihydroxyurs-11-ene, two (B and C) of 3beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…[102] Buddlejasaponin I, IV and the sulfated saikosaponin (sandrosaponin I), which were isolated from B. rigidum, exhibited a very potent in-vivo anti-inflammatory effect (1 mg/ear dose) on mouse ear oedema induced by PMA compared with the equivalent dose of indometacin. The effect of these compounds on other inflammatory parameters [109] Rotundioside F (-) Acute inflammation [109] Rotundioside A, H, I, J Cytotoxic against MK-1, HeLa and B16F10 cell lines [30,110] B. salicifolium Polyacetylenes derivatives Antibacterial [111,112] B. scorzonerifolium Acetone extract Cytotoxic against A549 cell line [113][114][115] Wogonin, eugenin, saikochromone A (-) IL-2 [50] Saikosaponin B3, bupleurosides III, VI, IX and XIII and scorzonerosides A, B, C…”
Section: B Rigidummentioning
confidence: 99%
See 2 more Smart Citations
“…[102] Buddlejasaponin I, IV and the sulfated saikosaponin (sandrosaponin I), which were isolated from B. rigidum, exhibited a very potent in-vivo anti-inflammatory effect (1 mg/ear dose) on mouse ear oedema induced by PMA compared with the equivalent dose of indometacin. The effect of these compounds on other inflammatory parameters [109] Rotundioside F (-) Acute inflammation [109] Rotundioside A, H, I, J Cytotoxic against MK-1, HeLa and B16F10 cell lines [30,110] B. salicifolium Polyacetylenes derivatives Antibacterial [111,112] B. scorzonerifolium Acetone extract Cytotoxic against A549 cell line [113][114][115] Wogonin, eugenin, saikochromone A (-) IL-2 [50] Saikosaponin B3, bupleurosides III, VI, IX and XIII and scorzonerosides A, B, C…”
Section: B Rigidummentioning
confidence: 99%
“…[75] The cytotoxic activity of both oleanane-type and ursanetype triterpene saponins isolated from B. rotundifolium by Fujioka and coworkers were examined in human gastric adenocarcinoma (MK-1), human cervical carcinoma (HeLa) and murine melanoma (B16F10) cell lines. [30,110] Among the monodesmosidic ursane-type saponins, rotundifoliosides A, H, I and J exhibited very potent cytotoxic activity with IC50 values in the range 11-71 mm. The highest activity was observed with rotundifolioside J, which had IC50 values of 16, 21 and 11 mm against the aforementioned cell lines, respectively.…”
Section: Cytotoxicity and Anti-tumour Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…8,9) Moreover, agricultural studies of the constituents of the seeds have been begun by Ono et al, 10) and studies of anti-proliferation of tumor cells have been initiated by Mihashi and colleagues. 11,12) In some areas in Kumamoto Prefecture, this plant is cultivated, and its aerial parts are discarded. We investigated the drug's constituents in conjunction with studies of the aerial parts of B. rotundifolium, which is cultivated for cut flowers, and the seeds of B. falcatum.…”
Section: Regular Articlementioning
confidence: 99%
“…HMBC analysis indicated that the sugar chain bonding connected with the C-3 of the sapogenol. Therefore, BFS-14 (11) was characterized as BRA-3 (13), BRA-5 (14), BRA-2 (15), BRA-4 (16), and BRA-7 (17) were identified as rotundifolioside J, 11,12) rotundifolioside I, 11,12) rotundioside E, 15,16) and rotundioside W, 11,12) and rotundioside V, 11,12) respectively. BRA-22 (18) (Table 5) showed a total of 48 carbon signals, of which 18 indicated the presence of a rhamnosyl-(1→2)-glucosyl-(1→2)-fucosyl moiety identical to that of BRA-3 (13).…”
Section: Regular Articlementioning
confidence: 99%